2013
DOI: 10.3144/expresspolymlett.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of phenylethynylcarbonyl terminated novel thermosetting imide compound

Abstract: Abstract. Phenylethynyl terminated novel imide compound based on 1,3-bis(3-aminophenoxy)benzene (APB) and phenylethynyl trimellitic anhydride (PETA) were prepared. The curing behavior of phenylethynyl terminated imide compound was investigated by differential scanning calorimetry and Fourier transform infrared spectrometry. The curing reaction of phenylethynylcarbonyl end group completed at 220°C, and proceeded much faster than that of phenylethynyl end group. Glass transition temperature of the thermosetting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The 1 H NMR spectrum contained aromatic protons characteristic of a pair of 1,4-disubstituted rings (7.30e7.26 and 7.24e7.20 ppm) representing the influence of the cyanate and the isopropylidene moieties respectively. Similarly, the 13 C NMR spectrum represented a pure compound: the signal to noise ratio was high and all of the chemical shifts were accounted for e the characteristic cyanato carbon visible at 109 ppm [33].…”
Section: Characterisation Of the Monomersmentioning
confidence: 99%
“…The 1 H NMR spectrum contained aromatic protons characteristic of a pair of 1,4-disubstituted rings (7.30e7.26 and 7.24e7.20 ppm) representing the influence of the cyanate and the isopropylidene moieties respectively. Similarly, the 13 C NMR spectrum represented a pure compound: the signal to noise ratio was high and all of the chemical shifts were accounted for e the characteristic cyanato carbon visible at 109 ppm [33].…”
Section: Characterisation Of the Monomersmentioning
confidence: 99%
“…Cured articles were produced by the casting method using the imide compounds having phenylethynyl carbonyl groups at both terminal ends. From results of differential scanning calorimetry (DSC) measurements under the same conditions as previously reported, curing conditions of 200°C/3 hours + 220°C/3 hours were determined for PECI‐133APB and PECI‐134APB and curing conditions of 200°C/3 hours + 250°C/3 hours were determined for PECI‐34DPE.…”
Section: Methodsmentioning
confidence: 99%
“…We already synthesized a novel thermosetting imide compound having phenylethynyl carbonyl groups and examined the curing behavior thereof and the characteristics of the obtained cured article . As a result, we found that the thermosetting imide compound having phenylethynyl carbonyl groups can reduce the curing temperature (approximately 370°C) of the phenylethynyl group by approximately 150°C.…”
Section: Introductionmentioning
confidence: 99%
“…For the crosslinked polymers, mechanical properties in the viscoelastic state are related to the network structure. Then, their crosslink density can be determined from Equation (5) [34,35], which was also used by other authors for the determination of the crosslink density for highly crosslinked imidecompounds [8] (Equation (5)):…”
Section: Viscoelastic Behavior and Crosslink Densitymentioning
confidence: 99%
“…60-80 wt%) brings difficulties for investigation of the curing kinetics of these resins by thermal analysis. Some authors report the determination of the curing kinetics of polyimides using FTIR or NMR analysis [6][7][8][9]. Detecting the increase of the imide bands intensity during the chemical reaction, the conversion can be determined with quite high accuracy.…”
mentioning
confidence: 99%